Maternity and professional life: The case of the female journey of students at a federal education institution - Souza, Marcela Ingrid Mendes; Dornelas , Myriam Angélica; Barbosa , Rosemary Costa e (Seven Editora, 2024)
Today's women take care of the children, the house, work outside the home and in some cases, study, which is clearly something to be proud of, however, being a mother can be a barrier in your professional life. The general objective of this study was to analyze the perception of students of the Bachelor's Degree in Business Administration of a federal educational institution about how motherhood affects professional life. Methodologically, a qualitative research of a descriptive nature was carried out using the case study method. This study used secondary data that consisted of the bibliographic research developed for the construction of the theoretical framework of the present study and the primary data was given through the application of a semi-structured questionnaire to 86 students of the Administration Course of a federal educational institution. In the results, most of the students answered that having children makes it difficult to carry out professional activities, however, those who are already mothers answered that it is possible to reconcile the maternity journey with studies. In fact, it is possible to reconcile motherhood with other activities, but for this to happen, some factors are necessary that can contribute to the permanence of these mothers in the labor market. DOI:https://doi.org/10.56238/sevened2023.007-081